A GA-based parameters tuning method for an ADRC controller of ISP for aerial remote sensing applications. (October 2018) - Zhou, Xiangyang; Gao, Hao; Zhao, Beilei; Zhao, Libo
Abstract: This paper presents a parameters tuning method based on the genetic algorithm (GA) for an active disturbance rejection control (ADRC) of a three-axis inertially stabilized platform (ISP) with imaging sensors. To improve the stabilization accuracy and robustness of an aerial ISP under multi-source disturbances environment, an ADRC control scheme is first proposed. Then, to accurately identify and tune the parameters in the ADRC controller, a GA-based parameters tuning method is proposed. In this way, the performance of the ADRC is superior to the empirical method. To validate the proposed method, the simulations and experiments are carried out. The results show that the proposed ADRC with GA-based parameters tuning method has significant disturbance rejection ability which can improve the stabilization accuracy obviously. Compared with the ADRC with empirically tuning method, the stabilization error (RMS) under movable base is decreased up to 50.09%. Highlights: An ADRC control scheme is proposed to improve the stabilization accuracy and disturbance rejection ability of an ISP. A GA-based parameters tuning method is proposed to accurately identify and tune the parameters of the ADRC controller. The empirical parameters tuning method and the proposed GA-based method are both applied in the work as a comparison. Simulations and experiments are carried out to validate the proposed method.